A Combined Approach Using Patch-Clamp Study and Computer Simulation Study for Understanding Long QT Syndrome and TdP in Women - Furukawa, Tetsushi (Bentham Science Publishers Ltd., 2008)
Female sex is an independent risk factor for development of torsade de pointes (TdP)-type arrhythmias in both congenital and acquired long QT syndrome (LQTS). In females, QT(c) interval and TdP risk vary during the menstrual cycle and around delivery. Biological experiments including single-cell current recordings with the patch-clamp technique and biochemical experiments show that progesterone modulates cardiac K(+) current and Ca(2+) current via the non-genomic pathway of the progesterone receptor, and thus the cardiac repolarization duration, in a concentration-dependent manner. Incorporation of these biological findings into a computer model of single-cell and coupled-cell cardiomyocytes simulates fluctuations in QT(c) interval during the menstrual cycle with reasonable accuracy. Based on this model, progesterone is predicted to have protective effects against sympathetic nervous system-induced arrhythmias in congenital LQTS and drug-induced TdP in acquired LQTS. A combined biological and computational approach may provide a powerful means to risk stratify TdP risk in women.